Pemanfaatan Media Sosial Instagram dalam Meningkatkan Kemampuan Berpikir Kreatif Siswa dan Implikasnya dalam Layanan Bimbingan dan Konseling di SMP DARUL AMAN - Hafizah, Adinda; Putri, Ade Chita; Salsabila, Syafani; Dewi, Apriana; Amara, Vida; Harahap, Muhammad Aliyafi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study aims to see how counseling teachers use Instagram social media to improve students' creative thinking abilities. Activities carried out by BK teachers and students on Instagram social media are also part of guidance and counseling services, so this research wants to see the implications of these activities in guidance and counseling services. The research method used is a qualitative case study because this research focuses on the use of Instagram media at Darul Aman Middle School. Data collection techniques used are interviews and observation. The results of this study are the first that this study found that there are activities that involve counseling teachers and students in Instagram social media that can increase creativity. The implications of these activities are expanding the range of services, facilitating access to information, increasing student participation, improving service quality. Keywords: Guidance and counseling, Instagram social media, creative thinking skills, guidance and counseling services